"Teleswallowing": a case study of remote swallowing assessment. Issue 3 (6th July 2015) - Nick Harrop, Dr; Bidmead, Elaine; Reid, Tilly; Marshall, Alison; Southern, Veronica
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Telemedicine has enabled speech and language therapists (SLTs) to remotely assess swallowing difficulties (dysphagia) experienced by nursing home residents. The new technique, "teleswallowing", was designed by the Speech and Language Therapy Service at Blackpool Teaching Hospitals NHS Foundation Trust. It allows prompt assessment, avoiding potential risks of aspiration pneumonia, malnutrition, poor rehabilitation, increased hospital stays and reduced quality of life (Hinchey et al., 2005; Langmore et al., 1998). The purpose of this paper is to report on a second pilot of teleswallowing and the concomitant adoption study. Design/methodology/approach – The adoption study employed qualitative methods, including consultations with senior managers, semi-structured interviews with nursing home matrons/managers and nurses, two focus groups and semi-structured interviews with SLTs. The project clinical lead kept an activity log, which was used to estimate resource savings. Findings – Over a three-month period, six SLTs and 17 patients in five nursing homes participated in teleswallowing assessments. Teleswallowing benefited both patients and participating nursing homes. Better use of therapist time and cost savings were demonstrated and evidence showed that the service could be successfully scaled up. Despite this, a number of barriers to service transformation were identified. Originality/value – This is the first implementation of teleswallowing in the UK, but it has been used in Australia (Ward et al., 2012). The approach to engaging stakeholders to understand and address barriers to adoption is novel. The value lies in the lessons learned for future innovations.